Indonesian-English Code Switching Used on Pitaâ€™s Life Youtube Channel - Heda, Ayuni Kabobu; Ena, F.X. Ouda Teda (IJOLTL (Indonesian Journal of Language Teaching and Linguistics), 2021)
YouTube is one of the popular social media nowadays. There are many content creator or known as YouTuber who shares their idea, experience, and creativity through YouTube video. The use of language styles such as code-switching become a trend. In this study, the researcher aims to analyze the reasons and social function of why the speaker of YouTube video uses code-switching in their vlog. In conducting this research, the researcher uses document analysis and qualitative research in analyzing the data. The subject of this study is one video taken from Pitaâ€™s lifeâ€™s channel YouTube entitled â€œSehari sebelum dilarang pemerintah keluarâ€. As the result, the researcher found out that there are some reasons that influence the speaker in using code-switching, they are; talking about a particular topic, doing interjection, being emphatic to something, classifying the speech content, and lack of vocabulary. The social factors that affect her are, marrying a foreign man, living in a multilingual society, and most of her subscribers are from her country of origin.